دور المرأة الريفية في تثمين التراث و تخليد الملاحم والأعياد الوطنية - إيمان قريب; أمينة بوعامر; د/رندة بوسعيد (جامعة عمار ثليجي الاغواط, 2025)
الملخص : تهدف هذه الدراسة إلى إبراز الدور الحيوي الذي تؤديه المرأة الريفية في الحفاظ على التراث الثقافي وتخليد الملاحم والأعياد الوطنية من خلال مشاركتها الفعّالة في مختلف الأنشطة الثقافية والإعلامية التي تنظمها المؤسسات، خاصة دور الثقافة. اعتمدت الدراسة على منهج وصفي تحليلي مدعوم بدراسة ميدانية استُعمل فيها الاستبيان كأداة رئيسية لجمع البيانات من عينة من النساء الريفيات بولاية الأغواط. أظهرت النتائج أنّ المرأة الريفية تساهم بشكل كبير في نقل التراث للأجيال القادمة من خلال الفنون الشعبية، الحرف اليدوية، العادات والتقاليد، إضافة إلى مشاركتها الفاعلة في الاحتفالات الوطنية والأنشطة الثقافية. كما بينت النتائج أنّ أهم التحديات التي تواجهها تتمثل في ضعف الدعم المؤسسي، قلة الموارد، وصعوبة التنقل. وتخلص الدراسة إلى أنّ تثمين التراث الوطني وتعزيز المشاركة الثقافية للمرأة الريفية يتطلب مزيدًا من الدعم المادي والمعنوي، مع توفير فضاءات أوسع للتمكين الثقافي والاجتماعي. الكلمات المفتاحية: المرأة الريفية، التراث الثقافي، الأعياد الوطنية، المؤسسات الثقافية، المشاركة المجتمعية. Abstract: This study aims to highlight the vital role played by rural women in preserving cultural heritage and commemorating national epics and celebrations through their active participation in various cultural and informational activities organized by institutions, particularly cultural centers. The research relied on a descriptive-analytical method supported by a field study, using a questionnaire as the main tool for data collection from a sample of rural women in Laghouat Province. The findings revealed that rural women significantly contribute to transmitting heritage to future generations through popular arts, handicrafts, customs, and traditions, in addition to their active participation in national celebrations and cultural events. The results also showed that the main challenges they face include weak institutional support, limited resources, and mobility difficulties. The study concludes that valuing national heritage and enhancing rural women’s cultural participation requires greater material and moral support, along with providing broader spaces for cultural and social empowerment. Keywords: Rural women, cultural heritage, national celebrations, cultural institutions, community participation.
المشاركة في ألايام الاعلامية للمؤسسات الثقافية